PENANGGULANGAN COVID-19 DALAM KERANGKA TEORI KEPENDUDUKAN MALTHUS - Aswatini Raharto (Jurnal Kependudukan Indonesia, 2020)
This paper was not necessarily discussing COVID-19 as Malthus' positive check, but it examines the current efforts to overcome and control the COVID-19 pandemic as a preventive and positive check. COVID-19 gives credence to the Malthusian Theory of Population.Â  The key features of this model are that the preventive checks that should be carried out by men are not only limited to controlling the population through family planning but also to control the pressure on the existing resources. The two forces will act to restore equilibrium: preventive check and positive check. From the Malthusian theory, herd immunity in the time of COVID-19 regarded as a positive check. As Indonesia's home to more than 270 million population, the mortality rate likely uncontrollable. Thus herd immunity should not be chosen as a policy option.